Blastic plasmacytoid dendritic cell neoplasm with leukemic presentation: 10‐Color flow cytometry diagnosis and HyperCVAD therapy. Issue 3 (11th January 2016) - Deotare, Uday; Yee, Karen W.L.; Le, Lisa W.; Porwit, Anna; Tierens, Anne; Musani, Rumina; Barth, David; Torlakovic, Emina; Schimmer, Aaron; Schuh, Andre C.; Seftel, Matthew; Minden, Mark D.; et al.
Abstract : Few studies describe the comprehensive immunophenotypic pattern of blastic plasmacytoid dendritic cell neoplasm (BPDCN) in the bone marrow and its treatment. This retrospective analysis evaluates the diagnostic flow cytometry (FCM) pattern and outcome of nine patients diagnosed with BPDCN. A four‐tube 10‐color FCM panel used for diagnosis of acute leukemia (AL), showed cells in the blast gate (CD45dim/low SSC) and were positive for CD4(bright), CD33(dim), CD56(heterogenous), CD123(bright), CD36, CD38, HLA‐DR, CD71. Seven patients received front‐line induction therapy with HyperCVAD with an overall response rate of 86%. Five of six responders underwent planned allogeneic hematopoietic cell transplantation (allo‐HCT). For a median follow up of 13.3 months, the 1‐year disease free survival and overall survival were 56 and 67%, respectively. An accurate diagnosis of BPDCN can be made by 10‐color FCM using a four‐tube AL panel demonstrating a characteristic pattern of antigen expression. Front‐line induction chemotherapy with HyperCVAD can yield high remission rates, but allo‐HCT is required for long‐term durable remissions. Am. J. Hematol. 91:283–286, 2016. © 2015 Wiley Periodicals, Inc.